WILL (When to Induce Labour to Limit risk in pregnancy hypertension): a multicentre randomised controlled trial — adaptations to deliver a timing-of-birth trial during the COVID-19 international pandemic - Laura A. Magee; Sue Tohill; Katie Kirkham; Ruth Evans; Eleni Gkini; Catherine A. Moakes; Clive Stubbs; Jim Thornton; Peter von Dadelszen; the WILL Trial Study Group (Trials, 2022)
Abstract Background As a pragmatic randomised timing-of-birth trial, WILL adapted its trial procedures in response to the COVID-19 pandemic. These are reviewed here to inform post-pandemic trial methodology. Methods The trial (internal pilot) paused in March 2020, re-opened in July 2020, and is currently recruiting in 37 UK NHS consultant-led maternity units. We evaluated pandemic adaptations made to WILL processes and surveyed sites for their views of these changes (20 sites, videoconference). Results Despite 88% of sites favouring an electronic investigator site file (ISF), information technology requirements and clinical trial unit (CTU) operating procedures mandated the ongoing use of paper ISFs; site start-up delays resulted from restricted access to the CTU. Site initiation visits (SIVs) were conducted remotely; 50% of sites preferred remote SIVs and 44% felt that it was trial-dependent, while few preferred SIVs in-person as standard procedure. The Central team felt remote SIVs provided scheduling and attendance flexibility (for sites and trial staff), the option of recording discussions for missing or future staff, improved efficiency by having multiple sites attend, and time and cost savings; the negative impact on rapport-building and interaction was partially mitigated over time with more familiarity with technology and new ways-of-working. Two methods of remote consent were developed and used by 30/37 sites and for 54/156 recruits. Most (86%) sites using remote consenting felt it improved recruitment. For remote data monitoring (5 sites), advantages were primarily for the monitor (e.g. flexibility, no time constraints, reduced cost), and disadvantages primarily for the sites (e.g. document and access preparation, attendance at a follow-up meeting), but 81% of sites desired having the option of remote monitoring post-pandemic. Conclusions COVID adaptations to WILL trial processes improved the flexibility of trial delivery, for Central and site staff, and participants. Flexibility to use these strategies should be retained post-pandemic. Trial registration ISRCTN77258279. Registered on 05 December 2018.